Study on the damage of Zr63.5Cu23Al9Fe4.5 amorphous and crystalline alloys by Fe, He ions beam irradiation - Li, Na; Zhang, Peng; Hao, Jinhua; Zhang, Lisong; Zhang, Xiaonan; Qiang, Jianbing; Li, Huaying; Mei, Xianxiu (Journal of alloys and compounds, 2024)
In order to study the physical mechanism of the effect of complex fusion irradiation environment on Zr-based amorphous alloys, simultaneous irradiation with Fe and He ions was performed on Zr63.5Cu23Al9Fe4.5 amorphous and crystalline alloys at room temperature. Single Fe ions irradiation and single He ions irradiation were used for comparison to investigate the influence of synergistic effects as well as intrinsic structural differences on irradiation-induced microstructural evolution and mechanical properties. It was been found that the irradiated amorphous alloys maintained its amorphous structure without nanocrystallization or elemental segregation. However, the irradiated region of the crystalline alloys experienced full amorphization, forming amorphous structure with bright contrast (Al-rich) and dark contrast (Cu-rich or Fe-rich). Under single He ions irradiation and simultaneous Fe+He ions irradiation conditions, He bubbles generated in both amorphous and crystalline alloys, where He bubbles in amorphous alloys distributed homogeneously, while the Cu-rich region of crystalline alloys exhibited larger sizes of He bubbles. Compared to single He ions irradiation, the size of He bubbles was larger, the atomic arrangement was more disordered (for amorphous alloys) and the element distribution was more homogeneous (for crystalline alloys) after simultaneous irradiation. Compared to single Fe ions irradiation, simultaneous irradiation induced slightly greater swelling. After irradiation, obvious softening was observed in both alloys, and the hardness of amorphous alloys was as follows: unirradiated > single He ions irradiation ≈ single Fe ions irradiation ≈ simultaneous Fe+He ions irradiation, while that of crystalline alloys was as follows: unirradiated > single He ions irradiation > single Fe ions irradiation ≈ simultaneous Fe+He ions irradiation. The serrated flow behavior of amorphous alloys weakened and the deformation was more homogeneous. As a result of irradiation-induced amorphization, serrated flow phenomenon also occurred in crystalline alloys, however, this type of inhomogeneous amorphous structure showed much weaker serrated flow behavior than the homogeneous amorphous structure. This study provides a deeper understanding of the irradiation damage mechanism of Zr-based amorphous alloys in complex irradiation environments. •Synergistic effect of Fe+He ions dual-beam irradiation on Zr-based alloy was studied.•Irradiation effect of same-component Zr-based amorphous and crystalline were studied.•Bubble/swelling was larger in Fe+He irradiation than in single He/Fe irradiation.•Amorphization with inhomogeneous elements occurred in irradiated crystalline alloy.•Inhomogeneous amorphous structure showed higher hardness and weaker serrated flow.